Does proptosis effect the meibography in patients with thyroid eye disease? - Berk Ergun, Şule; Şimşek, Dilmeran (Acta Medica, 2024)
Objective: The study aimed to compare the meibographies of the eyes of patients with thyroid eye disease who have varying degrees of proptosis. Materials and Methods: Charts of patients with thyroid eye disease between January 2019 to January 2022 were retrospectively reviewed. Patients with mild and inactive thyroid eye disease, and with 1 mm or more difference in measurements of Hertel exophthalmometer between the eyes were included in the study. The eye of each patient with higher proptosis was included in the study group while the other eye with lower proptosis was included in the control group. The area of meibomian gland loss was evaluated using meibography (Sirius; CSO, Florence, Italy). Results: Total of 28 eyes of 14 patients were evaluated. Mean meibomian gland dropout area for the upper eyelid was 17.91± 15.37% in the study group and 14.43± 8.61% in the control group. Mean meibomian gland dropout area for the sum of upper and lower eyelid was 44.76± 23.16% in the study group and 43.03± 21.59% in the control group. Mean meibomian gland dropout area for the upper eyelid and also for the sum of upper and lower eyelid were higher in the study group than the control group; however, these results were not significant (p=0.540 and 0.865, respectively). On the other hand, the Pearson correlation test results suggested a significant correlation between the two groups; for the upper eyelid (p<0.001, r=+0.670) and also for the sum of upper and lower eyelids (p<0.001, r=+0.768). Conclusion: This study showed differences regarding meibographic changes between control and study group. Further studies with larger series are needed to confirm these results.